Induction of erythroid differentiation of murine erythroleukemia cells by nicotinamide and related compounds. - Terada, M (1979)
Nicotinamide and its analogues were evaluated for their activity as inducers of differentiation of murine erythroleukemia cells in culture. N'-Methylnicotinamide was the most effective of the compounds tested; at its optimal concentration it was more effective than dimethyl sulfoxide. With 8-10 mM N'-methylnicotinamide, almost all the cells contained hemoglobin (benzidine-reactive) after a 60-hr culture. Commitment to differentiate, assayed by transfer of the cells to semisolid medium without inducers, occurred much earlier and was more extensive with N'-methylnicotinamide than that with dimethyl sulfoxide or nicotinamide. Increase in globin mRNA was greater in the cells cultured with N'-methylnicotinamide than in cells cultured with dimethyl sulfoxide or nicotinamide. The relationship between the inducing activities of nicotinamide analogues and their effect on poly(ADP-ribose) polymerase in vitro was studied. All the compounds studied that had strong inhibitory effects on poly(ADP-ribose) polymerase in vitro induced differentiation of erythroleukemia cells in culture. This property is not a prerequisite of inducers; N'-methylnicotinamide did not inhibit the enzyme in vitro.